In-vivo Sino-Atrial Node Mapping in Children and Adults With Congenital Heart Disease - Kharbanda, Rohit K.; van Schie, Mathijs S.; Ramdat Misier, Nawin L.; Wesselius, Fons J.; Zwijnenburg, Roxanne D.; van Leeuwen, Wouter J.; van de Woestijne, Pieter C.; de Jong, Peter L.; Bogers, Ad J. J. C.; Taverne, Yannick J. H. J.; de Groot, Natasja M. S. (Frontiers in Pediatrics, 2022)
Background: Sinus node dysfunction (SND) and atrial tachyarrhythmias frequently co-exist in the aging patient with congenital heart disease (CHD), even after surgical correction early in life. We examined differences in electrophysiological properties of the sino-atrial node (SAN) area between pediatric and adult patients with CHD. Methods Epicardial mapping of the SAN was performed during sinus rhythm in 12 pediatric (0.6 [0.4–2.4] years) and 15 adult (47 [40–55] years) patients. Unipolar potentials were classified as single-, short or long double- and fractionated potentials. Unipolar voltage, relative R-to-S-amplitude ratio and duration of all potentials was calculated. Conduction velocity (CV) and the amount of conduction block (CB) was calculated. Results SAN activity in pediatric patients was solely observed near the junction of the superior caval vein and the right atrium, while in adults SAN activity was observed even up to the middle part of the right atrium. Compared to pediatric patients, the SAN region of adults was characterized by lower CV, lower voltages, more CB and a higher degree of fractionation. At the earliest site of activation, single potentials from pediatrics consisted of broad monophasic S-waves with high amplitudes, while adults had smaller rS-potentials with longer duration which were more often fractionated. Conclusions Compared to pediatric patients, adults with uncorrected CHD have more inhomogeneous conduction and variations in preferential SAN exit site, which are presumable caused by aging related remodeling. Long-term follow-up of these patients is essential to demonstrate whether these changes are related to development of SND and also atrial tachyarrhythmias early in life.